Attitudes toward evidence-based clinical practice among doctors of chiropractic with diplomate-level training in orthopedics - Roecker, Christopher B (BioMed Central, 2013)
BACKGROUND: Evidence-based clinical practice (EBCP) is a practice model gaining prominence within healthcare, including the chiropractic profession. The status of EBCP has been evaluated in a variety of healthcare disciplines, but little is known regarding the attitudes doctors of chiropractic (DCs) hold toward this model of healthcare. This project examines the attitudes toward EBCP within a specialty discipline of DCs. METHODS: We identified a survey questionnaire previously used to evaluate EBCP among non-chiropractic complementary and alternative practitioners. We adapted this questionnaire for use among DCs and pretested it in 5 chiropractic college faculty. The final version was administered to DCs with diplomate-level training in orthopedics. The survey was emailed to 299 potential participants; descriptive results were calculated. RESULTS: 144 surveys were returned, resulting in a 48% response rate. The majority of respondents perceived EBCP as an important aspect of chiropractic practice. Respondents also believed themselves to have an above average skill level in EBCP, reported that training originated from their diplomate education, and based the majority of their practice on clinical research. CONCLUSION: Doctors of chiropractic with an orthopedic diplomate appear to have favorable attitudes toward EBCP. Further study will help understand EBCP perceptions among general field DCs. A logical next step includes validation of this questionnaire.